ID 295 – Deep repetitive transcranial magnetic stimulation with the H-coil in Alzheimer's disease: A placebo-controlled, double-blind study. Issue 3 (March 2016) - Coppi, E.; Ferrari, L.; Nuara, A.; Chieffo, R.; Houdayer, E.; Bernasconi, M.P.; Falautano, M.; Ambrosi, A.; Zangen, A.; Comi, G.; Magnani, G.; Leocani, L.
Abstract : Objective: Focal rTMS in Alzheimer's disease (AD) revealed cognitive benefits. H-coil depolarize deeper and wider structures compared with focal coils, maybe targeting widespread networks involved in neurodegenerative disorders. We explored H-coil safety and efficacy in AD. Methods: Thirty AD subjects (70.21 ± 8.66 y.o.), randomized in real or sham groups, underwent 16 rTMS sessions (3/week for 4 weeks, 1/week for other 4 weeks), over fronto-parieto-temporal lobes (10 Hz). Neuropsychological assessment was performed at baseline, after 4 weeks (4 w), at the end (8 w). Primary outcome: improvement in Alzheimer's disease Scale-cognitive (ADAS-cog). Four subjects were excluded (1 acute myocardial infarction in the sham group, 1 misdiagnosis, 2 missing data), thus statistical analysis included 26 subjects. Results: No serious side effects were reported. At 4 w, percent ADAS-cog improvement from baseline (4 w%) was greater in the real compared with the sham group ( p  = 0.042). The relationship between baseline ADAS-cog and 4 w% differed between the two groups ( p  = 0.009), with higher improvement for less cognitively impaired subjects at baseline only after real stimulation. Conclusions: Excitatory deep rTMS appears feasible in AD with a promising safety and efficacy profile and may better impact the course of the disease when administered at earlier stages.